Potential of Lactic Acid Bacteria From Tape and Jember Tempeh as a Probiotic Candidate - Siti Nur Azizah; Mikhania Christiningtyas Eryani; Azizah Azizah (Jurnal Biodjati, 2021)
Probiotics are microbes in fermented foods that have beneficial effects on health. Microbes that act as probiotics are lactic acid bacteria (LAB) that can produce metabolites such as lactic acid, hydrogen peroxide, and bacteriocins. This study aimed to obtain lactic acid bacterial isolates from tape and tempeh, and to test the potential of LAB as a probiotic candidate by activity test as an antidiarrhea and its resistance to gastric pH and bile salts. The fermentation products used as a source of LAB isolates are tempeh sumber mas merk, and yellow cassava tape, sari madu merk from Jember. The results of the first stage regarding the isolation of LAB using GYP media showed that there were 2 LAB isolates (TaJ.14 and TaJ.15) from the tape and 4 LAB isolates (TeJ.18, TeJ.22, TeJ.24, and TeJ.25) from tempeh. The results of the antidiarrheal test using the disc diffusion method (oxoid) showed that TaJ.14 and TaJ.15 isolates were able to inhibit Bacillus subtilis, Escherichia coli, and Shigella dysentriae, while TeJ.18, TeJ.22, TeJ.24, TeJ.25, and Lactobacillus casei (control) was only able to inhibit B. subtilis and E. coli. The results of LAB resistance to gastric pH showed that the TeJ.25 isolate had the highest percentage of pH 3 and 2.5 resistance (51.13 and 33.03%) compared to other isolates and controls. LAB resistance test results against bile salts (oxgal) showed that the TeJ.22 isolate had the highest percentage of resistance (75.10%) compared to other isolates although was still higher in control (75.99%).